Medicolegal evaluation of violence against women in the Ottoman Empire with the light of qadi registry records between the 17th and 20th centuries - Selcuk Cetin; Bedirhan Sezer Oner (Medicine Science)
Violence against women is still a widespread human rights violation and public health problem around the world. The aims of this study were to evaluate the violence against women between the 17th and 20th centuries in Ottoman Empire and discuss the findings with current literature in Turkiye and worldwide concerning violence against women. A total of 10 volumes of qadi registry records (QRR), covering the period between the 17th and 20th centuries (1659–1921), were examined. These records, published as part of the Metropolitan Municipality Cultural Publications and prepared under the editorship of Prof. Dr. I.S., were analyzed in detail. Sections pertaining to violence against women were identified within the QRR, and relevant data regarding their content were extracted for the study. Among the 5326 qadi registry records examined, 89 cases were related to cases regarding violence against women. It was determined that 36 (40.4%) of the 89 cases were victims of physical violence, 30 (33.7%) of them were victims of sexual violence, 13 (14.6%) of them were victims of verbal violence and 10 (11.2%) of them were victims of economic violence. The data on violence against women that we found in the qadi registry records of the Ottoman Empire between the 17th and 20th centuries will contribute to understanding the historical process of this issue, in a historical process where resources and information on this subject are quite limited. [Med-Science 2025; 14(1.000): 248-60]